Pengembangan Kerangka Kerja Sosiokultural untuk Membangun Karakter Islami di Program Studi Pendidikan Bahasa Inggris - Astri Hapsari (Universitas Islam Indonesia, 2015)
A unique department which integrates Islamic psychology and values within its curriculum, Department of English Language Education Universitas Islam Indonesia develops Islamic learning activity model from Vygotskyan sociocultural perspective in educational psychology. This paper will elaborate how Vygotskyan sociocultural framework shapes the Islamic character building in English language teaching and learning conducted by the lecturers in the classrooms and extracurricular activities conducted by the students, taking references within educational linguistics that understand language from the perspective of sociocultural theory “on the role of language and other sociocultural artefacts in the mediation of human activity and social practice” (Cross, 2009). The aims of the discussion are to connect the dots of sociocultural perspective in practice in language education, Islamic character building, and educational psychology.